Analysis of structural transformations in natural quartzites under the influence of gamma irradiation - Bereznyak, E.P.; Dikiy, N.P.; Kolodiy, I.V.; Medvedeva, E.P.; Khodyreva, Yu.S. (Вопросы атомной науки и техники, 2021)
Using the methods of IR spectroscopy, crystal-optical and XRD analysis the evolution of the structure of Ovruch deposit natural quartzites under the influence of γ-irradiation in the range of absorbed doses (Dabs = 10⁶…3.5⋅10⁷ Gy) has been researched. The elemental composition of natural quartzites was determined by the gamma activation method on a linear electron accelerator. It was found that as a result of irradiation the crystal structure of quartz, which forms the basis of quartzite, is improved due to radiation annealing of the defects in the initial structure. At the same time crystallization of amorphous silica, which fringes large grains of quartz, occurs with its transformation into fine-crystalline quartz. These processes do not lead to cracking in the quartzite rock. Obtained data indicates a high radiation resistance of the Ovruch deposit quartzites and confirms the prospects of using this geological formation as a natural barrier for the construction of radioactive waste long-term storage.